Mechanomyographic and electromyographic responses to stimulated and voluntary contractions in the dorsiflexors of young and old men - Shima, Norihiro; McNeil, Chris J.; Rice, Charles L. (Muscle & nerve, 2007)
The effect of age on mechanomyography (MMG) has not been examined for electrically evoked contractions. Similar to torque, we expected that postactivation potentiation of the MMG would differ between young and old subjects. Additionally, under voluntary conditions, we compared normalized MMG and electromyographic (EMG) signals in relation to torque, and expected that MMG, unlike EMG, would be affected by age. In 10 young and 10 old men, electrical stimulation was delivered before and after a 10‐s maximal voluntary contraction (MVC) to assess potentiation of contractile (twitch torque; Pt), electrical (M‐wave amplitude), and mechanical (MMG amplitude) properties of the dorsiflexors. Subsequently, subjects performed voluntary contractions at 20%, 40%, 60%, 80%, and 100% MVC for calculation of normalized MMG–torque and EMG–torque relationships. Following the MVC, Pt and evoked MMG were larger than at rest in both groups, but M‐wave amplitude was unchanged. Twitch potentiation was greater in young than old, whereas evoked MMG was unaffected by age. Under voluntary conditions, values for MMG and EMG were similar between groups, except for greater MMG at MVC in young men. The shape of MMG and EMG relationships to torque was similar only in young men. Using the aging model, our results indicate that potentiation of the mechanical components (MMG) differ from those of twitch torque. Furthermore, the comparison of normalized voluntary MMG with age provides additional support for the concept of age‐related motor unit remodeling. Muscle Nerve, 2006